Chemical Environment Influence the Incidence of Childhood Autism: A Review - Yu, Rong-Rong; Xu, Yun; Wang, Yong-Gu; Qiu, Fei-Yue (Asian Journal of Chemistry, 2013)
This review summarizes the environmental factors in particular chemicals involved in autism with either increasing or reducing effect in disease incidence, which will be helpful for prevention and treatment of the disease.